Comparative effectiveness of ACE inhibitors spirapril, fosinopril, and enalapril in complex therapy of patients with coronary heart disease, chronic obstructive pulmonary disease, and arterial hypertension - M. A. Popova; N. N. Terentyeva (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study effectiveness of ACE inhibitor therapy in coronary heart disease (CHD) combined with chronic obstructive pulmonary disease (COPD). Material and methods. In total, 89 males with CHD and COPD were examined. All participants had Stage I-II arterial hypertension (AH). For antihypertensive therapy correction and secondary prevention of heart failure, ACE inhibitors were administered (spirapril, fosinopril, and enalapril), combined with dihydropyridine calcium antagonists and M-cholinolytics. ACE inhibitor therapy lasted for 12 weeks. At baseline and during the treatment, 24-hour blood pressure monitoring was performed, mean pulmonary artery pressure (MPAP), lung function, endothelium-dependent and independent vasoreactivity, hemorheology parameters, and quality of life (QoL) were measured. Results. In CHP and COPD patients, ACE inhibitors spirapril and fosinopril were more effective than enalapril. The first two agents demonstrated positive effects on vasoreactivity and hemorheology, facilitating facilitated decrease in systemic and pulmonary hypertension, as well as QoL improvement. After 12 weeks of the therapy, spirapril decreased MPAP by 16.4%, fosinopril - by 6.5%, enalapril – by 2.8%. Fibrinogen and hematocrit levels decreased by 18.7% and 13.4%, respectively, after spirapril therapy, by 5.8% and 9.2% after fosinopril therapy, and by 4.1% and 4.8%, respectively, after enalapril therapy. Conclusion. In complex calcium antagonist and M-cholinoblocker therapy among CHD and COPD patients, an ACE inhibitor spirapril is the most effective agent.